Long reads and Hi-C sequencing illuminate the two-compartment genome of the model arbuscular mycorrhizal symbiont Rhizophagus irregularis - Yildirir, Gökalp (The New phytologist, 2022)
© 2021 The Authors. New Phytologist © 2021 New Phytologist Foundation.